2022
DOI: 10.1007/s10811-022-02692-4
|View full text |Cite
|
Sign up to set email alerts
|

A new cyanobacterial species with a protective effect on lettuce grown under salinity stress: Envisaging sustainable agriculture practices

Abstract: In this work, a new terrestrial cyanobacterial species, Oculatella lusitanica LEGE 161147, was isolated and characterized using a polyphasic approach. Morphologically, O. lusitanica shares characteristics with different Oculatella species (mainly with O. crustae-formantes), lacking distinctive features. However, the phylogeny based on the 16S rRNA gene sequence and the 16S-23S ITS secondary structures support the establishment of this isolate as a new species. O. lusitanica is placed within a clade mainly comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The type genus of the family, Oculatella , is mostly a soil genus (Becerra‐Absalón et al, 2020; Jung et al, 2020; Mikhailyuk et al, 2022; Osorio‐Santos et al, 2014; Vinogradova et al, 2017). Other taxa were found in subaerial habitats such as caves (Chakraborty et al, 2021; Zammit et al, 2012) or wet walls or hard man‐made substrates such as clay pots (Brito et al, 2022; Mai et al, 2018). A few taxa have been described from aquatic environments (Jahodářová, Dvořák, Hašler, Holušová, & Poulíčková, 2017; (Jahodářová, Dvořák, Hašler, & Poulíckova, 2017; Osorio‐Santos et al, 2014; Strunecký et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type genus of the family, Oculatella , is mostly a soil genus (Becerra‐Absalón et al, 2020; Jung et al, 2020; Mikhailyuk et al, 2022; Osorio‐Santos et al, 2014; Vinogradova et al, 2017). Other taxa were found in subaerial habitats such as caves (Chakraborty et al, 2021; Zammit et al, 2012) or wet walls or hard man‐made substrates such as clay pots (Brito et al, 2022; Mai et al, 2018). A few taxa have been described from aquatic environments (Jahodářová, Dvořák, Hašler, Holušová, & Poulíčková, 2017; (Jahodářová, Dvořák, Hašler, & Poulíckova, 2017; Osorio‐Santos et al, 2014; Strunecký et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…nuda, Til. torsiva, (Mai et al, 2018), and Oculatella lusitanica (Brito et al, 2022). Soils are similar to but harsher than subaerial habitats, yet they numerous species in the family Oculatellaceae, including, in the genus Oculatella, O.…”
Section: 7mentioning
confidence: 99%
“…Likewise, Naorem and Udayana 140 considered cyanobacteria as add-ons of the beneficial soil microbiota to remediate salt-affected soils under organic farming. In a recent report, Brito et al 141 showed that the soil application of a new terrestrial cyanobacterial species ( Oculatella lusitanica LEGE 161147) on lettuce ( Lactuca sativa L. cv Marvel of Four Seasons) had a limited priming effect. However, there were beneficial effects by mitigating the deleterious salinity stress by eliciting non-enzymatic antioxidant ( i.e.…”
Section: Amelioration Of Saline and Sodic Soils By Microalgae And Cya...mentioning
confidence: 99%
“…Moreover, photosynthetic pigments, relative water, stability of membrane, carbohydrates, proline, ascorbic acid, glutathione, N, P, and K+ion content, superoxide dismutase, and catalase activities were also stimulated compared to control plants. Furthermore, Brito et al ( 2022 ) found that the cyanobacterial species Oculatella lusitanica LEGE stimulated salinity stress resistance in lettuce plants by increasing the non-enzymatic antioxidant system (H 2 O 2 , proline, and reduced glutathione). Regarding drought cases, soils inoculated by Spirulina meneghiniana and Anabaena oryzae improved lettuce plants’ growth as compared with non-inoculated soil plants (Ibraheem, 2007 ).…”
Section: Role Of Cyanobacteria In Agriculturementioning
confidence: 99%